An Evaluation on the Compliance to Safety Helmet Usage among Motorcyclists in Batu Pahat, Johor - Ambak, Kamaruddin; Hashim, H.; Yusoff, I.; David, B. (International Journal of Integrated Engineering, 2011)
This paper presents methods on how to determine the level of practice of usage of safety helmet among motorcyclist in Batu Pahat and to identify the target group who are most likely to violate the safety helmet law among. A questionnaire study was carried out in urban and rural Batu Pahat. A total of 185 respondents were interviewed and the data was analyzed using the statistics. Six variables were found to be significant at percent level (p<0.05): gender, education level, type of safety helmet, distance of travel, riding experience and location of travel. Practice of safety helmet usage among motorcyclist in Batu Pahat was found to be higher for female riders, higher educated riders, full shell helmet users, travelling at a distance of 1 km to 10 km, riders having good practice and riders in the town area. All the variables above are contributing factors in the practice of helmet usage among motorcyclists in Batu Pahat. Subsequently, the road safety programs and enforcement teams should be more focused on male riders, rider with low education levels, half shell helmet riders, 10 km and below distance, riding experience for 10 years above and rural riders based on their lower practice of using safety helmet.